Immunotherapy of hepatocellular carcinoma - Greten, Tim (Henry Stewart Talks, 2017)
Hepatocellular carcinoma (HCC) background and overview, Non-alcoholic steatohepatitis (NASH) and HCC, Immune suppressor mechanisms in tumour environments, Ongoing and future immunotherapy trials in HCC
Archived at 2023/06/29